The Influence of Content Marketing, Online Customer Reviews, and Ratings on Purchase Intention through Brand Image as a Mediating Variable - Larasati; Purmono, Bintoro Bagus (Lentera Barasaki Publishing House, 2023)
This research examines the relationship between content marketing, online customer review, and rating towards the brand image and its impact on the purchase intention of Flimty on the official Flimtyfiber TikTokShop account. The research uses a causal-comparative method with a quantitative approach. The respondents in this study are individuals throughout Indonesia aged at least 17 years old who are familiar with Flimty but have yet to purchase it before or have purchased similar products to Flimty from other brands and have a TikTok account. The sampling technique employs non-probability sampling, specifically purposive sampling. Data was collected by distributing questionnaires through a Google Form with 205 respondents. Hypotheses were tested using the Structural Equation Model (SEM) with the assistance of AMOS 24 software. The research findings show that content marketing, online customer review, and rating significantly influence brand image. Online customer review and rating have a significant impact on purchase intention. Content marketing doesn't impact purchase intention. Brand image can mediate the relationship between content marketing and rating with purchase intention. Brand image can't mediate the relationship between online customer review and purchase intention.